Identification of Novel Genetic Variants in CVID Patients With Autoimmunity, Autoinflammation, or Malignancy - Christiansen, Mette; Offersen, Rasmus; Jensen, Jens Magnus Bernth; Petersen, Mikkel Steen; Larsen, Carsten S.; Mogensen, Trine H. (Frontiers in Immunology, 2020)
.Common variable immunodeficiency (CVID) is a primary immunodeficiency characterized by recurrent bacterial infections and defined by reduced levels of IgG, IgA and/or IgM, insufficient response to polysaccharide vaccination, and an abnormal B cell immunophenotype with significantly reduced fraction of isotype-switched memory B cells. In addition to this infectious phenotype, at least one third of the patients experience autoimmune, autoinflammatory, granulomatous and/or malignant complications. The very heterogenous presentation strongly suggest a collection of different disease entities with somewhat different pathogenesis, and most likely diverse genetic etiologies. Major progress has been made during recent years with the advent and introduction of next generation sequencing, initially for research purposes, but more recently for clinical practice. In the present study we performed whole exome sequencing on twenty CVID patients with autoimmune, autoinflammatory, and/or malignancy from the Danish CVID cohort with the aim to identify gene variants with a certain, possible or potential disease-causing role in CVID. Through bioinformatics analyses, we identified variants with possible/probable disease-causing potential in nine of the patients. Of these, three patients had 4 variants classified as likely pathogenic (NFKB1, TNFAIP3 and TTC37), whereas in six patients we identified 7 variants of possible pathogenic potential classified as variants of unknown significance (STAT3, IL17F, IRAK4, DDX41, NLRC3, TNFRSF1A, and PLCG2). In the remainder eleven patients, we did not identify possible genetic causes. Genetic findings were correlated to clinical disease presentation, clinical immunological phenotype, and disease complications. We suggest that the variants identified in the present work should lay the ground for future studies to functionally validate their disease-causing potential and to investigate at the mechanistic and molecular level their precise role in CVID pathogenesis. Overall, we believe that the present work contributes with important new insights into the genetic basis of CVID, and particular in the subset of CVID patients with a complex phenotype involving not only infection, but also autoimmunity, autoinflammation, and malignancy.